Fluorescence quenching reaction of chlorophyll a by tris(acetylacetonate)iron(III) in various solvents - Nararak Leesakul; Daweena Masen; Grampp, Guenter (Penerbit Universiti Kebangsaan Malaysia, 2017)
Chlorophyll a is known as the prevailing light absorbing pigment giving a strong absorption and fluorescence emission in visible region. Quenching reactions of the chlorophyll a fluorescence by Fe(acac)3 were precisely investigated in various organic solvents which are benzene toluene, ethanol, methanol, dmf, dmso and acetonitrile. Electron transfer performance of chlorophyll a by Fe(acac)3 was investigated from oxidative quenching reaction. Herein, the simplified Rehm-Weller relationship was used to calculate the free energy change of the photo-induced electron transfer reaction. Emission intensity decreased when the concentration of Fe(acac)3 quencher was increased. Non-linear Stern-Volmer plots are found to be affected by inner filter effect more than the ground state complex formation. Rate of quenching reactions (kq) were determined from the Stern-Volmer equation with corrected inner filter effect. The rates of quenching reactions occurred faster in high viscous solvents.